Mixed strain pathogen populations accelerate the evolution of antibiotic resistance in patients - Wheatley, R; MacLean, R (University of Oxford, 2023)
This is the source data file for the manuscript "Mixed strain pathogen populations accelerate the evolution of antibiotic resistance in patients" accepted at Nature Communications.